2000
DOI: 10.1152/jn.2000.83.5.2905
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia But Not Anoxia Evokes Vesicular and Ca2+-Independent Glutamate Release In the Dorsal Vagal Complex In Vitro

Abstract: Whole cell recordings of fura-2 dialyzed vagal neurons of brain stem slices were used to monitor interstitial glutamate accumulation within the dorsal vagal complex. Anoxia produced a sustained outward current (60 pA) and a moderate [Ca(2+)](i) rise (40 nM). These responses were neither mimicked by [1S,3R]-1-aminocyclo-pentane-1, 3-dicarboxylic acid nor affected by Ca(2+)-free solution, 6-cyano-7-nitroquino-xaline-2,3-dione (CNQX), 2-amino-5-phosphonovalerate (APV), or tetrodotoxin. Anoxia or cyanide in glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 60 publications
6
27
0
1
Order By: Relevance
“…Spontaneous release includes both AP-dependent and AP-independent components (Figure 1), with AP-dependent components comprising larger amplitudes than the AP-independent miniatures. In this paper, we first show that H/H caused an increase in the frequency, but not the amplitude, of AP-independent release (Figure 2), as shown by others in CA1 pyramidal neurons (Katchman and Hershkowitz, 1993), neocortical neurons (Fleidervish et al, 2001), and in brainstem cells (Kulik et al, 2000). Although it is possible that there are large-amplitude, TTX-resistant miniatures that contain several presynaptic vesicles, due to the sum of several quanta (Llano et al, 2000), we did not observe large-amplitude sEPSCs in TTX experiments.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Spontaneous release includes both AP-dependent and AP-independent components (Figure 1), with AP-dependent components comprising larger amplitudes than the AP-independent miniatures. In this paper, we first show that H/H caused an increase in the frequency, but not the amplitude, of AP-independent release (Figure 2), as shown by others in CA1 pyramidal neurons (Katchman and Hershkowitz, 1993), neocortical neurons (Fleidervish et al, 2001), and in brainstem cells (Kulik et al, 2000). Although it is possible that there are large-amplitude, TTX-resistant miniatures that contain several presynaptic vesicles, due to the sum of several quanta (Llano et al, 2000), we did not observe large-amplitude sEPSCs in TTX experiments.…”
Section: Discussionsupporting
confidence: 74%
“…The resting potential was À64.3±5.6 mV in the control and À63.0±5.3 mV during H/H; AP threshold was À42.2±1.1 mV in the control and À40.3 ± 3.0 mV in H/H; AP amplitude was 83.4±8.1 mV in the control and 83.4±4.1 mV in H/H. Although changes in input resistance could occur during longer (up to 6 mins) hypoxic/ischemic episodes (Zhang and Krnjevic, 1993;Fleidervish et al, 2001;Kulik et al, 2000), we did not observe any significant change in the input resistance (178.8±49.4 MO in the control and 183.1±51.1 MO in H/H, P > 0.05; Figure 4C) during the short H/H challenge. Therefore, the enhanced glutamatergic response during transient ischemia was not due to intrinsic property changes in the patched postsynaptic neurons.…”
Section: Enhanced Ap-dependent Spontaneous Release During Transient Imentioning
confidence: 96%
“…Real time glutamate measurement in an in vitro model of ischemia showed that glutamate uptake is inhibited within a few minutes of the onset of ischemia (Jabaudou et al 2000). The Na + -dependent glutamate transporter of the plasma membrane fails to remove glutamate under this condition, instead, by a reverse operation, it mediates the release of glutamate (Nicholls and Attwell 1990;Kulik et al 2000;Rossi et al 2000). The driving force for the reverse operation of the glutamate transporter is the increased intracellular Na + concentration resulting mainly from a persistent depolarization and Na + entry via non-inactivating Na + channels (see Urenjak and Obrenovitch 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Oxygen deprivation may activate cellular mechanisms that allow neurons to adapt to metabolic stress and to survive for a certain period. A shift in metabolic pathways (16), expression of cell-protective proteins (17), and changes in neuronal excitability through modulating ion channels (13,14) or neurotransmitter releases (18) are some of the survival strategies. This study suggests that the PDGF-BB / PDGFR-β signal is one neuroprotective strategy for cell survival against hypoxia by depressing the excitatory synaptic transmission in the NTS neurons, resulting in modulation of the hypoxic ventilatory response.…”
Section: +mentioning
confidence: 99%